2009
DOI: 10.1128/cvi.00213-09
|View full text |Cite
|
Sign up to set email alerts
|

Simple and Rapid Lateral-Flow Assay for the Detection of Foot-and-Mouth Disease Virus

Abstract: A simple lateral-flow assay (LFA) based on a monoclonal antibody (MAb 70-17) was developed for the detection of foot-and-mouth disease virus (FMDV) under nonlaboratory conditions. The LFA was evaluated with epithelial suspensions (n ‫؍‬ 704) prepared from current and historical field samples which had been submitted to the Pirbright Laboratory (United Kingdom) and from negative samples (n ‫؍‬ 100) collected from naïve animals in Korea. Four FMDV serotypes (type O, A, Asia 1, and C) were detected in the LFA, bu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
29
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(30 citation statements)
references
References 17 publications
0
29
0
1
Order By: Relevance
“…These results demonstrate that Ag-ELISA detecting FMDV is an accurate method for taking rapid measurements at the site of a suspected footand-mouth disease outbreak in Asia before confirmation of the disease diagnosis in the laboratory, thereby offering the possibility of implementing control procedures more rapidly. 15 Other study demonstrated that 3ABC ELISA (C-ELISA) developed in Denmark was 71% sensitive and 90% specific at the recommended cutoff. These results have important implications if the tests are to be used to screen herds or individual cattle in surveillance programs, at border crossings for importexport clearance, or following emergency vaccination in an outbreak situation.…”
Section: Discussionmentioning
confidence: 99%
“…These results demonstrate that Ag-ELISA detecting FMDV is an accurate method for taking rapid measurements at the site of a suspected footand-mouth disease outbreak in Asia before confirmation of the disease diagnosis in the laboratory, thereby offering the possibility of implementing control procedures more rapidly. 15 Other study demonstrated that 3ABC ELISA (C-ELISA) developed in Denmark was 71% sensitive and 90% specific at the recommended cutoff. These results have important implications if the tests are to be used to screen herds or individual cattle in surveillance programs, at border crossings for importexport clearance, or following emergency vaccination in an outbreak situation.…”
Section: Discussionmentioning
confidence: 99%
“…Als Zielsequenzen für den chipbasierten Nachweis von MKSV dienen ein 128 Basenpaare (bp) langes Fragment aus der hochkonservierten Region der internen ribosomalen Eintrittsstelle (IRES) und ein 88 bp langes Fragment aus der konservierten Region der RNA‐Polymerase (3D) 1,9. So lässt sich eine Probe zeitgleich auf alle sieben Serotypen untersuchen.…”
Section: Das Mks‐virus Im Biochipunclassified
“…17 Many methods of single signature assays for detecting NSP antibodies have been used, including agar gel immunodiffusion, 18 the latex bead agglutination test, 19 enzyme-linked immunoelectrotransfer blot, 20,21 enzyme-linked immunosorbent assay (ELISA), 4,18,22e28 and chromatographic strip assay. 29,30 For FMDV-SP diagnosis, different immunoassay formats have been established such as the virus neutralization test, liquid-phase blocking ELISA, solid-phase blocking ELISA, and competition ELISA. 4,31,46 Recombinant antigens and synthetic peptides derived from FMDV SPs and NSPs have been developed as an alternative to the inactivated virus antigen.…”
Section: Introductionmentioning
confidence: 99%